Analisis Posisi Keuangan PT. Unilever Pada Industri Produk Rumah Tangga Periode 2019-2021 - Budi Dharma; Selvira Wardani Tanjung; Reni Yusnita (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
The purpose of this research is to conduct an analysis process on the financial performance of PT Unilever Indonesia, Tbk during the period 2019-2021 which is assessed based on the ratio of solvency, liquidity, activity, and profitability, by applying several financial ratio techniques. In terms of liquidity ratios, debt-to-assets and capital ratios, as well as its activities, this company is classified as â€œnot goodâ€, because the average value generated in the last three years is below the average of other companies in general. While the total asset turnover ratio shows a value that is classified as "good", because it is above the company's standard value in general. The profitability ratio, which consists of the ratio of return on assets and the ratio of return on equity, is in the category of "good" financial performance, while when viewed from the net profit margin, it is classified in the category of "poor" financial performance compared to the company's industry average in general.